TINJAUAN TERHADAP DISKRESI PENYIDIK KEPOLISIAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM (STUDI KASUS DI KEPOLISIAN RESOR BADUNG) - Budiawan, Kadek Setia; Tjatrayasa, I Made; Purwani, Sagung Putri M.E (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013)
Special protection is given to children in conflict with the law children and childrenwhoare victims of crime. Police as protector of society has discretion authority toprovide protection to children in conflict with the law. Implementation of the policeinvestigator's discretion to children in conflict with the law is very useful to be appliedin order children avoid punishment because application of criminal be the last option ifit can not be solved by other means.
Keywords: discretion, police, children in conflict with the law, punishment.